2015
DOI: 10.5487/tr.2015.31.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Cornus officinalis Methanol Extract Upregulates Melanogenesis in Melan-a Cells

Abstract: Cornus officinalis is widely distributed in Korea, and its fruit has been used to make as herbal drug for traditional medicine in Korea, Japan, and China because of its tonic, analgesic, and diuretic properties. However, the effects of C. officinalis methanol extract (COME) on melanogenesis remain poorly understood. We evaluated the melanogenic capability of COME in melan-a cells, which are immortalized mouse melanocytes. COME increased melanin synthesis in a dose-dependent manner. Treatment with 12.5 μg/mL of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The results of the present study revealed that C. fructus significantly inhibited CYP2E1 expression and activity. Previous studies suggested that C. fructus contained many active components, such as flavones (quercetin and kaempferol), organic acids, phenolic acids (gallic acid and tannic acid), iridoid glycosides, saponins, and other chemical components [29,30]. In the present study, the methanolic extract of C. fructus is rich in phenols (153.88 ± 1.26 mg/g) and flavones (51.69 ± 0.66 mg/g).…”
Section: Discussionmentioning
confidence: 61%
“…The results of the present study revealed that C. fructus significantly inhibited CYP2E1 expression and activity. Previous studies suggested that C. fructus contained many active components, such as flavones (quercetin and kaempferol), organic acids, phenolic acids (gallic acid and tannic acid), iridoid glycosides, saponins, and other chemical components [29,30]. In the present study, the methanolic extract of C. fructus is rich in phenols (153.88 ± 1.26 mg/g) and flavones (51.69 ± 0.66 mg/g).…”
Section: Discussionmentioning
confidence: 61%
“…Total RNA was isolated using the TriZol reagent (Life Technologies; Gaithersburg, MD), and the cDNA was prepared using M-MLV reverse transcriptase (Gibco-BRL; Gaithersburg, MD) according to the manufacturer's instructions [39] , [40] . The following primers were used for the amplification of human c-FLIP, Mcl-1, PSMA5, and actin: c-FLIP (sense) 5′- CGG ACT ATA GAG TGC TGA TGG -3′ and (antisense) 5′- GAT TAT CAG GCA GAT TCC TAG -3′, Mcl-1 (sense) 5′- GCG ACT GGC AAA GCT TGG CCT CAA-3′ and (antisense) 5′- GTT ACA GCT TGG ATC CCA ACT GCA-3′, PSMA5 (sense) 5′- CTT GCA AGA AGT TTA TCA CAA GTC T -3′ and (antisense) 5′- GAA ATT CTG GCC AGG CTG C -3′, and actin (sense) 5′- GGC ATC GTC ACC AAC TGG GAC -3′ and (anti-sense) 5′- CGA TTT CCC GCT CGG CCG TGG -3′.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium dodecyl sulfate, however, is a detergent with no reported antibacterial activity [18]. Other components, such as pegylated hydrogenated castor oils, are detergents used in the cosmetic industry with no reported antibacterial activity [19] but a negative impact on keratinocyte viability [20]. Cetylpyridinium chloride possesses antimicrobial activity, is used in oral rinses [21, 22], and has a negative impact on L929 fibroblast viability [23].…”
Section: Introductionmentioning
confidence: 99%